H2S-induced S-sulfhydration of pyruvate carboxylase contributes to gluconeogenesis in liver cells - Ju, YoungJun; Untereiner, Ashley; Wu, Lingyun; Yang, Guangdong (Biochimica et biophysica acta, 2015)
Cystathionine gamma-lyase (CSE)-derived hydrogen sulfide (H2S) possesses diverse roles in the liver, affecting lipoprotein synthesis, insulin sensitivity, and mitochondrial biogenesis. H2S S-sulfhydration is now proposed as a major mechanism for H2S-mediated signaling. Pyruvate carboxylase (PC) is an important enzyme for gluconeogenesis. S-sulfhydration regulation of PC by H2S and its implication in gluconeogenesis in the liver have been unknown. Gene expressions were analyzed by real-time PCR and western blotting, and protein S-sulfhydration was assessed by both modified biotin switch assay and tag switch assay. Glucose production and PC activity was measured with coupled enzyme assays, respectively. Exogenously applied H2S stimulates PC activity and gluconeogenesis in both HepG2 cells and mouse primary liver cells. CSE overexpression enhanced but CSE knockout reduced PC activity and gluconeogenesis in liver cells, and blockage of PC activity abolished H2S-induced gluconeogenesis. H2S had no effect on the expressions of PC mRNA and protein, while H2S S-sulfhydrated PC in a dithiothreitol-sensitive way. PC S-sulfhydration was significantly strengthened by CSE overexpression but attenuated by CSE knockout, suggesting that H2S enhances glucose production through S-sulfhydrating PC. Mutation of cysteine 265 in human PC diminished H2S-induced PC S-sulfhydration and activity. In addition, high-fat diet feeding of mice decreased both CSE expression and PC S-sulfhydration in the liver, while glucose deprivation of HepG2 cells stimulated CSE expression. CSE/H2S pathway plays an important role in the regulation of glucose production through S-sulfhydrating PC in the liver. Tissue-specific regulation of CSE/H2S pathway might be a promising therapeutic target of diabetes and other metabolic syndromes. •H2S stimulates PC activity and gluconeogenesis in liver cells.•H2S S-sulfhydrated PC in a dithiothreitol-sensitive way.•Cysteine-265 is essential for H2S-induced PC S-sulfhydration and activity.•High-fat diet decreased both CSE expression and PC S-sulfhydration in mouse liver.